2010
DOI: 10.1111/j.1472-4642.2010.00703.x
|View full text |Cite
|
Sign up to set email alerts
|

A hitchhiker’s guide to the Maritimes: anthropogenic transport facilitates long‐distance dispersal of an invasive marine crab to Newfoundland

Abstract: Aim  To determine timing, source and vector for the recent introduction of the European green crab, Carcinus maenas (Linnaeus, 1758), to Newfoundland using multiple lines of evidence.Location  Founding populations in Placentia Bay, Newfoundland, Canada and potential source populations in the north‐west Atlantic (NWA) and Europe.Methods  We analysed mitochondrial and microsatellite genetic data from European and NWA populations sampled during 1999–2002 to determine probable source locations and vectors for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 29 publications
5
97
2
Order By: Relevance
“…Local adaptation in the native range in Europe may have contributed to the green crab's explosive expansion throughout the northern East Coast of North America. Our results support the hypothesis that secondary invasion from a northern source may have facilitated C. maenas' northward spread in the East Coast by introducing cold-adapted genotypes (Roman, 2006;Blakeslee et al, 2010). In a broader context, this example illustrates the potential importance of locally adapted populations in allowing a species to survive novel conditions.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Local adaptation in the native range in Europe may have contributed to the green crab's explosive expansion throughout the northern East Coast of North America. Our results support the hypothesis that secondary invasion from a northern source may have facilitated C. maenas' northward spread in the East Coast by introducing cold-adapted genotypes (Roman, 2006;Blakeslee et al, 2010). In a broader context, this example illustrates the potential importance of locally adapted populations in allowing a species to survive novel conditions.…”
Section: Discussionsupporting
confidence: 76%
“…This initial invasive population slowly spread north and south, to range between southern Nova Scotia and coastal Virginia (Carlton and Cohen, 2003). In the 1980s, the range of C. maenas rapidly advanced north through the Maritime Provinces of Canada, spreading to northern Nova Scotia, Prince Edward Island, and finally to Newfoundland in 2007 (Roman, 2006;Blakeslee et al, 2010). Genetic analysis revealed that this rapid northward expansion was concurrent with a second introduction of the species from northern Europe (Roman, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This site has characteristics that predispose it to anthropogenic transport of Carcinus; the 2007 sampling was in a small fishing port where both bait transport and water discharge are potential vectors. Moreover, there is strong evidence that anthropogenic transport is responsible for the spread of Carcinus from Nova Scotia to eastern Newfoundland, suggesting that anthropogenic transport might also be important within our study area (27). Regardless of the mechanisms contributing to stochastic dispersal, its magnitude is likely to aid in the persistence of southern haplotypes in the population.…”
Section: Discussion Of the Carcinus Systemmentioning
confidence: 84%
“…Initial records of green crab in North America date back to 1817 in the New Jersey/New York area, with the species spreading northward to Maine by the early 1900's, and to the Bay of Fundy over the following 50 years (Audet et al 2003;Klassen and Locke 2007). Genetic analyses have also indicated that a separate introduction occurred along the eastern Scotian shelf in the 1980's (Roman 2006;Blakeslee et al 2010) which has resulted in a mixing of northern and southern European green crab genotypes. Evidence suggests that this mixing may have widened the species' environmental tolerance locally, likely contributing to physiological and behavioural changes across subpopulations (Blakeslee et al 2010, Rossong et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic analyses have also indicated that a separate introduction occurred along the eastern Scotian shelf in the 1980's (Roman 2006;Blakeslee et al 2010) which has resulted in a mixing of northern and southern European green crab genotypes. Evidence suggests that this mixing may have widened the species' environmental tolerance locally, likely contributing to physiological and behavioural changes across subpopulations (Blakeslee et al 2010, Rossong et al 2012. It is also thought that this genetic mixing may have accelerated the species' eastward spread along the Nova Scotian coast (Blakeslee et al 2010) despite prevalent downstream current systems (Brickman 2014;Gharouni et al 2017).…”
Section: Introductionmentioning
confidence: 99%